Targeting, Cascading, and Indirect Tax Design. Issue 2 (19th August 2014) - Keen, Michael James
Abstract : Purpose: This paper addresses two fundamental issues in indirect tax design. It first revisits the case for reduced rates on items especially important to the poor, and then explores the welfare costs from cascading taxes Design/methodology/approach: Applied theory Findings: On the first issue, the paper establishes conditions under which even very crudely targeted spending measures better serve the interests of the poor than does reduced taxation of particular commodities looming large in their consumption. On the second, it shows that these may actually be lower the wider the set of inputs that are taxed but, more to the point, may plausibly be large even at a low nominal tax rate and with relatively few stages of production: contrary to a common mantra, "a low rate on a broad base" is not always good policy. Originality/value: Both issues addressed in the paper are recurrent and central concerns in the design of indirect taxes in general, and the VAT/GST in particular. I am not aware of other treatments at all comparable in perspective or results. I hope the analysis will prove useful in many contexts where these issues arise - not least in India, where these issues are central to discussions of VAT/GTS reform